DESCRIPTIVE ANALYSIS ON THE USE OF MONITOR HYPOTHESIS ON ENGLISH ADULT LEARNER - Burhanudin Rais (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2021)
This study aims to describe the use of the monitor hypothesis in adult learner. This research is focused on the English spoken language. This study was conducted with descriptive analysis methods. This method was carried out by describing the results of the findings found in the data obtained. In collecting the data, the researcher used observation notes and sound recordings. The results of this study found that the learner was included to the over user monitor. Where he always corrected and was very careful when he wanted to make a sentence. Then, the results of this study also found that the sentence that learner made was always based on his thinking in Indonesian language. In other words, translating Indonesian language into English.